Assessing Assessment Literacy and Practices among Lecturers - Rezvani Kalajahi, Seyed Ali; Abdullah, Ain Nadzimah (Pedagogika, 2016)
Accountability systems are important for higher education and are often linked to the credibility of assessment literacy of lecturers. Lecturers are responsible for ‘report cards’ that act as benchmarks of student learning processes and outcomes. Therefore, assessment literacy of lecturers is of prior importance as institutions rely on lecturers to assess students’ content knowledge and skills. The question that arises is whether lecturers have been provided sufficient and appropriate knowledge of assessment methods or whether assessment has been left much to the idiosyncrasies of the lecturers. This study seeks to establish the level of assessment literacy among lecturers and investigate common assessment practices. The methodology involves a survey questionnaire administered to 65 lecturers from different disciplines at a Malaysian public university. Findings show that the state of assessment literacy among lecturers is not at a satisfactory level and that lecturers may have not gone through sufficient assessment training to discharge an important part of their professional responsibility in the context of teaching and learning.